Kepemimpinan Spiritualitas Musa Sebagai Dasar Bagi Pembinaan Asrama Di Sekolah Tinggi Theologia Ebenhaezer - Aris Elisa Tembay; Eliman; Ferdinan Pasaribu (Sekolah Tinggi Theologia Ebenhaezer Tanjung Enim, 2022)
Leadership begins with a spritual personal ability possessed, demonstrated through roles and functions, manifested in a moral form that can inspire the lives of others. This means that leadership that can generate trust for others is not only built by authority or spiritual factors solely in an office and power but by exemplary. Talking about leadership in the context of believers is certainly closely related to the moral responsibility that is possessed. This is not only the standard in building one's identity as a spiritual human being that first needs to be achieved and can build, awaken the people around him. The development of self-quality becomes a pattern that strategically improves leadership